PENDEKATAN ETNOPEDAGOGI DALAM PENGEMBANGAN BAHAN AJAR MENULIS KARYA ILMIAH DI SMA - Karyani Tri Tialani; Yusak Hudiyono; Widyatmike Gede Mulawarman; Susilo, Susilo; Bibit Suhadmady; Syaiful Arifin (Journal of Innovation Research and Knowledge, 2025)
The multidimensional crisis in Indonesia over the past decade requires evidence-based solutions, particularly in the field of humanities, including education and teaching. As the world undergoes rapid and significant changes, education undoubtedly plays a crucial role in every transformation that occurs. Teaching materials are reshaping the role of teachers in the learning process. Teachers are no longer the sole source of knowledge but rather serve as guides. Modern learning activities today focus on student-centered learning, which aims to provide opportunities for students to actively engage in their education. The core issue lies in the implementation of scientific work materials with ethnopedagogical content, which incorporate local wisdom values. However, these efforts have yet to achieve the desired outcomes and continue to face numerous challenges. To address these problems, the author employs a method involving the analysis of teaching materials, the design and development of instructional content, the application of the Project-Based Learning (PjBL) model, and product evaluation at SMAN 1 Berau. The design model used in this study follows the ADDIE approach, which consists of Analysis, Design, Development, Implementation, and Evaluation. The results of the testing indicate that teaching materials developed using ethnopedagogical methods are highly effective and beneficial as supplementary learning resources